Evaluation of Rhomboid Intercostal Block in Video-Assisted Thoracic Surgery: Comparing Three Concentrations of Ropivacaine - Deng, Wei; Jiang, Chen-Wei; Qian, Ke-jian; Liu, Fen (Frontiers in Pharmacology, 2022)
Background: Ultrasound-guided rhombic intercostal block (RIB) is a novel regional block that provides analgesia for patients who have received video-assisted thoracoscopic surgery (VATS). The anesthetic characteristics of ultrasound-guided RIB with different concentrations of ropivacaine are not known. This research primarily hypothesizes that ultrasound-guided RIB, given in combination with the same volume of different concentrations of ropivacaine, would improve the whole quality of recovery-40 (QoR-40) among patients with VATS. Approaches: This double-blinded, single-center, prospective, and controlled trial randomized 100 patients undergoing VATS to receive RIB. One hundred patients who have received elective VATS and satisfied inclusion standards were fallen into four groups randomly: control group with no RIB and R0.2%, R0.3%, and R0.4%; they underwent common anesthesia plus the RIB with ropivacaine at 0.2%, 0.3%, and 0.4% in a volume of 30mL. Outcomes: Groups R0.2%, R0.3%, and R0.4% displayed great diversities in the overall QoR-40 scores and QoR-40 dimensions (in addition to psychological support) by comparing with the control group (Group C) (p<0.001 for all contrasts). Group R0.3% and R0.4% displayed great diversities in the overall QoR-40 scores and QoR-40 dimensions (in addition to psychological support) by comparing with the R0.2% group (p<0.001 for all contrasts). The overall QoR-40 scores and QoR-40 dimensions (physical comfort [p=0.585]) did not vary greatly between the Group R0.3% and R0.4% (p>0.05 for all contrasts). Group R0.2%, R0.3% and R0.4% showed significant differences in numerical rating scales (NRS) score region under the curve (AUC) at rest and on movement in 48 hours when compared with the Group C (p<0.001 for all contrasts). Group R0.3% and R0.4% displayed great diversities in NRS score AUC at rest and on movement in 48 hours when compared with the R0.2% group (p<0.001 for all contrasts). The NRS mark AUC at rest and on movement in 48 hours did not vary greatly between the Group R0.3% and R0.4% (p>0.05 for all contrasts). Conclusion: It was found that a dose of 0.3% ropivacaine is the best concentration for RIB for patients undergoing VATS. Through growing ropivacaine concentration, the analgesia of the RIB was not improved greatly.